Endoparasite Infections in Pet and Zoo Birds in Italy. (12th March 2012) - Papini, Roberto; Girivetto, Martine; Marangi, Marianna; Mancianti, Francesca; Giangaspero, Annunziata
Abstract : Faecal samples were individually collected from pet (n = 63 ) and zoo (n = 83 ) birds representing 14 orders and 63 species. All the samples were examined by faecal flotation technique. In a subgroup of samples (n = 75 ), molecular assays were also used to detect Cryptosporidium oocysts and Giardia duodenalis cysts. Overall, 35.6% of the birds harboured parasites (42.2% of zoo birds and 27% of pet birds), including Strongyles-Capillarids (8.9%), Ascaridia (6.8%), Strongyles (5.5%), G. duodenalis Assemblage A (5.3%), Coccidia (4.1%), Cryptosporidium (4%), Porrocaecum (2.7%), Porrocaecum -Capillarids (2%), and Syngamus -Capillarids (0.7%). The zoonotic G. duodenalis Assemblage A and Cryptosporidium were exclusively found in Psittaciformes, with prevalences of 10.3% and 7.7% within this bird group. Zoo birds were more likely to harbor mixed infections (OR = 14.81) and symptomatic birds to be parasitized (OR = 4.72). Clinicians should be aware of the public health implications posed by zoonotic G. duodenalis Assemblages and Cryptosporidium species in captive birds.